2005
DOI: 10.1130/g21341.1
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing a 180 yr record of natural and anthropogenic induced low-oxygen conditions from Louisiana continental shelf sediments

Abstract: Figure 1. Locations of four cores discussed herein. Locations of hypoxia zone frequency taken from Committee on Environment and Natural Resources (2000), based on measurements done by N. Rabalais since 1985.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 23 publications
3
49
0
Order By: Relevance
“…Together with previous authors (Nelsen et al, 1994;Blackwelder et al, 1996;Platon and Sen Gupta, 2001), Osterman (2003) observed that the combined percentage of three foraminiferal species (Pseudononion atlanticum, Epistominella vitrea and Buliminella morgani) was highest in surface sediment samples from hypoxic areas at mid-shelf depths (30-70 m) off Louisiana. She termed this percentage the PEB Index and used it to reconstruct trends in bottomwater oxygenation over a 180-year period (Osterman et al, 2005). Later, Osterman et al (2007) extended coverage of the PEB Index to other parts of the Lousiana shelf and also examined a much longer time period in three gravity cores, including one obtained within the modern hypoxic zone.…”
Section: Foraminiferasupporting
confidence: 77%
“…Together with previous authors (Nelsen et al, 1994;Blackwelder et al, 1996;Platon and Sen Gupta, 2001), Osterman (2003) observed that the combined percentage of three foraminiferal species (Pseudononion atlanticum, Epistominella vitrea and Buliminella morgani) was highest in surface sediment samples from hypoxic areas at mid-shelf depths (30-70 m) off Louisiana. She termed this percentage the PEB Index and used it to reconstruct trends in bottomwater oxygenation over a 180-year period (Osterman et al, 2005). Later, Osterman et al (2007) extended coverage of the PEB Index to other parts of the Lousiana shelf and also examined a much longer time period in three gravity cores, including one obtained within the modern hypoxic zone.…”
Section: Foraminiferasupporting
confidence: 77%
“…Fluctuations in the amount of these low-oxygen-tolerant species between 1817 A.D. and 1910 A.D. correspond with increased discharge/flooding events in the Mississippi River drainage. In most cases, high river discharge correlates with high percentage values of the low-oxygen-tolerant PEB species (Osterman et al, 2005).…”
Section: An Evaluation Of An Enclosed Methods For the Determination Ofmentioning
confidence: 99%
“…Measurements of Louisiana continental-shelf waters have indicated that hypoxia (oxygen content <2mg/L) has increased since 1985 (Rabalais et al, 1999). Sediment cores taken from the Louisiana shelf have provided a record of hypoxic and low-oxygen conditions over longer time intervals of 50-100 years (Sen Gupta et al, 1996;Blackwelder et al, 1996;Osterman et al, 2005).…”
Section: An Evaluation Of An Enclosed Methods For the Determination Ofmentioning
confidence: 99%
“…Extensive studies have shown that the loss comes from a combination of anthropogenic (e.g., artificial canal dredging, pond creation, and so forth) and natural mechanisms, involving relative sea level rise and wave attack on marshes fronting open water. While fossil records of low-oxygen-tolerant foraminifers suggest that the peak of hypoxia activity coincided with nutrient enhancement in the late 1950s, the peak also correlates well with the peak slope of wetland losses during the same time period [Osterman et al, 2005], so separating these effects remains difficult.…”
Section: River-dominated Marginsmentioning
confidence: 99%